2022
DOI: 10.1109/jtehm.2022.3174809
|View full text |Cite
|
Sign up to set email alerts
|

Design of an Affordable, Modular Implant Device for Soft Tissue Tension Assessment and Range of Motion Tracking During Total Hip Arthroplasty

Abstract: Background: In hip arthroplasties, surgeons rely on their experience to assess the stability and balance of hip tissues when fitting the implant to their patients. During the operation, surgeons use a modular, temporary set of implants to feel the tension in the surrounding soft tissues and adjust the implant configuration. This process is naturally subjective and therefore depends on the operator. Inexperienced surgeons undertaking hip arthroplasties are twice as likely to experience errors than th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…In this question, we classify the functions and techniques used to assess the movements of people undergoing hip arthroplasty. We found that the studies [8,12,13,22,23] argue that the main functions of inertial sensors are capable of measuring various aspects of motion, such as velocity, acceleration, and body orientation. A second paper [9] discusses the main functions performed by inertial sensors in patients who have undergone hip arthroplasty, such as (1) the measurement of gait kinematics and (2) the classification of gait in inertial sensors as normal gait, toe walking, heel walking, and assessment of balance during gait.…”
Section: Rq2-what Are the Main Functions Performed By Inertial Sensor...mentioning
confidence: 95%
See 4 more Smart Citations
“…In this question, we classify the functions and techniques used to assess the movements of people undergoing hip arthroplasty. We found that the studies [8,12,13,22,23] argue that the main functions of inertial sensors are capable of measuring various aspects of motion, such as velocity, acceleration, and body orientation. A second paper [9] discusses the main functions performed by inertial sensors in patients who have undergone hip arthroplasty, such as (1) the measurement of gait kinematics and (2) the classification of gait in inertial sensors as normal gait, toe walking, heel walking, and assessment of balance during gait.…”
Section: Rq2-what Are the Main Functions Performed By Inertial Sensor...mentioning
confidence: 95%
“…Refs. [8,22] indicate that an IMU-based intelligent hip testing system was used to measure the orientation and velocity of hip motion.…”
Section: Review Of the Literature To Map The Studiesmentioning
confidence: 99%
See 3 more Smart Citations